2019
DOI: 10.1101/855106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic patterns of introgression in interspecific populations created by crossing wheat with its wild relative

Abstract: 16Wild relatives of hexaploid wheat (Triticum aestivum) are the reservoirs of novel allelic 17 diversity with great potential to improve many agronomic traits in wheat. Here, we 18 investigated the genome-wide patterns and efficiency of Aegilops tauschii allele introgression 19 into the winter wheat cultivars. The introgression population of 351 BC 1 F 3 : 5 lines was 20 selected based on phenology and development characteristics from crosses between six 21 hexaploid wheat lines and 21 wheat-Ae. tauschii octop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…2B, label k) was introduced into the D subgenome of bread wheat. To date, there is no evidence showing that T. urartu contributed gene flow to bread wheat (Nyine et al 2020;Zhou et al 2020). This is possibly due to the low survival rate of unreduced gametes and hybrid offspring, as well as the narrow geographical distribution of ancestral diploid populations (Matsuoka 2011;Scott et al 2019).…”
Section: Speciation Through Homoploid Hybridization In Triticummentioning
confidence: 99%
See 3 more Smart Citations
“…2B, label k) was introduced into the D subgenome of bread wheat. To date, there is no evidence showing that T. urartu contributed gene flow to bread wheat (Nyine et al 2020;Zhou et al 2020). This is possibly due to the low survival rate of unreduced gametes and hybrid offspring, as well as the narrow geographical distribution of ancestral diploid populations (Matsuoka 2011;Scott et al 2019).…”
Section: Speciation Through Homoploid Hybridization In Triticummentioning
confidence: 99%
“…In many crops, such as rice (Meyer et al 2016) and soybean (Wang et al 2019), introgression from wild populations into cultivated species could increase the diversity of cultivated populations substantially. Many researches have demonstrated that the frequent introgression contributed to the restoration of genetic diversity in bread wheat (Cheng et al 2019;He et al 2019;Nyine et al 2020;Zhou et al 2020). Tetraploid introgression to hexaploid was more frequent and relatively recent, probably due to the higher survival rate of the offspring after homologous hybridization.…”
Section: Increasing the Genetic Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…tauschii donors in the synthetic subpopulation can vary substantially, from as little as 0.5% to as high as 43% of the D subgenome, a larger range than identified in studies using synthetic octoploids as primary Ae. tauschii donors (0.075 % to 13.5 %) 36 . Through comparison of sister lines within the panel we also show that the content of the donor genome is not necessarily linked to the number of subsequent crosses post introduction of primary synthetic material (SF6, ST4).…”
Section: Recent Synthetic Wheat Contribution To D Genome Variation Anmentioning
confidence: 99%